Identification and Characterization of Nodulation-Signaling Pathway 2, a Gene of Medicago truncatula Involved in Nod Factor Signaling - Oldroyd, Giles E.D. (American Society of Plant Biologists, 2003)
Bacterially derived Nod factor is critical in the establishment of the legume/rhizobia symbiosis. Understanding the mechanisms of Nod factor perception and signal transduction in the plant will greatly advance our understanding of this complex interaction. Here, we describe the identification of a new locus, nodulation-signaling pathway 2 (NSP2), of Medicago truncatula that is involved in Nod factor signaling. Mutants at this locus are blocked for Nod factor-induced gene expression and show a reduced root hair deformation response. nsp2 plants also show a complete absence of infection and cortical cell division following Sinorhizobium meliloti inoculation. Nod factor-induced calcium spiking, one of the earliest responses tested, is still functional in these mutant plants. We conclude that the gene NSP2 is a component of the Nod factor signal transduction pathway that lies downstream of the calcium-spiking response.